If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x)(2 + 3x) = 320 (2 * x + 3x * x) = 320 (2x + 3x2) = 320 Solving 2x + 3x2 = 320 Solving for variable 'x'. Reorder the terms: -320 + 2x + 3x2 = 320 + -320 Combine like terms: 320 + -320 = 0 -320 + 2x + 3x2 = 0 Factor a trinomial. (-32 + -3x)(10 + -1x) = 0Subproblem 1
Set the factor '(-32 + -3x)' equal to zero and attempt to solve: Simplifying -32 + -3x = 0 Solving -32 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -3x = 0 + 32 Combine like terms: -32 + 32 = 0 0 + -3x = 0 + 32 -3x = 0 + 32 Combine like terms: 0 + 32 = 32 -3x = 32 Divide each side by '-3'. x = -10.66666667 Simplifying x = -10.66666667Subproblem 2
Set the factor '(10 + -1x)' equal to zero and attempt to solve: Simplifying 10 + -1x = 0 Solving 10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 0 + -10 -1x = 0 + -10 Combine like terms: 0 + -10 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10Solution
x = {-10.66666667, 10}
| h(n-4)=-3n-4 | | 13m+4w=1223 | | x/12-18=31 | | 60+20m=720 | | 2x^2+2y^2-4x+4y+18=O | | 6(-7p-8)=-90 | | 3.2x-15=4x | | -3x=-5x+2(7+2) | | 17v+v-16v=20 | | 1+6(7p-7)=-335 | | 33-8p=-527 | | x^2+2x-3=129 | | -6z+3=3-z | | 17r-15r-2r+r=13 | | 17z+z-17z=14 | | (2x-10)=(x+25) | | .25(y+1)=2y-4(y-4) | | 20+2y+20=-8y-20 | | 7=-14 | | 7=-14b | | x^2y^2z^2/xyz | | x+6k=0 | | 34a-32a+8=96 | | 6(5^10)/3(5^8) | | -48=6s | | 4/5x^0 | | 7x-6x=90 | | 8s+2s+12-3s-10+-2-6s= | | 10+6z=3z-8 | | 6(5)^10/3(5)^8 | | -4=q-3.33 | | m/8=0.8 |